PENGARUH PENGGUNAAN SMARTPHONE DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA (Survey Kepada Peserta Didik Kelas 10 Dan 11 Jurusan Pemasaran SMK Negeri 1 Tasikmalaya Tahun Ajaran 2023/2024) - Ikhlas Maulana; Ati Sadiah; Raden Roro Suci Nurdianti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The main problem of this research is the low learning achievement results of students in grades 10 and 11 at SMK Negeri 1 Tasikmalaya. This research aims to determine the effect of smartphone use and learning discipline on student learning achievement. This research uses a quantitative approach with a survey method. The data collection technique is through distributing questionnaires with a population of 260 students at SMK Negeri 1 Tasikmalaya and the sampling technique uses a proportional sampling technique with a total of 145 students as respondents. Based on the results of this research, it shows that 1) smartphone use has a positive and significant effect on learning achievement. 2) learning discipline has a positive and significant effect on learning achievement.